DIFFUSION OF INNOVATIONS, KNOWLEDGE SPILLOVERS AND ECONOMIC GROWTH OF THE REGIONS OF KAZAKHSTAN: MUTUAL IMPACT - Spankulova L. S.; Kaneva M.A.; Chulanova Z.K. (Scientific Journal of Pedagogy and Economics, 2020)
In the transition from the raw material orientation of the economy to industrial development, an increase in innovative activity is of great importance. Diffusion of innovation and the knowledge spillovers between regions can play an active role in this. To stimulate innovative activity, which plays a decisive role in the transition from the raw material orientation of the economy to industrial development, diffusion of innovations and the knowledge spillovers between regions are important. The flows of technological innovations, stimulating the processes of creating new products and technologies, contribute to increasing the rate of regional economic growth. The purpose of the study is to quantify the impact of costs on R&D and technological innovation, their flows in space on the economic growth of the regions of Kazakhstan. The authors verified the models of endogenous growth for Kazakhstan, built a social filter, and calculated two specifications of the econometric model with fixed effects. Model calculations confirmed the hypothesis about the positive impact of technological innovation costs on regional economic growth rates. At the same time, the regions need to pursue their own innovation policy in order to maintain absorption capacity, which is a prerequisite for an effective flow of knowledge. The results of the study can be used by public authorities in the formation of the regional innovation policy of the Republic of Kazakhstan